The design and implementation of multi-node converters - Walters, David John (My University, 2010)
A switched mode power converter with an extremely wide output range could take the place of numerous other, less flexible, power converters that are only capable of operating at or near to a single output. However, when developing converters with wide output ranges there is a compromise between how effectively the converter‟s components can be utilised and the output range. This leads to converters with wide output ranges suffering from weight, cost and size penalties. This dissertation suggests a new converter architecture as a solution to this problem, where composite converters are implemented using multiple smaller converters (or nodes). The nodes can be connected in different series, parallel or series/parallel combinations, which allows the converter‟s components, and specifically its passive components, to be better utilised. This dissertation optimises the multi-node architecture using logical arguments and simulations coupled with a Genetic Algorithm. A prototype converter is then designed, analysed and built so that theoretical converter models can be experimentally verified